What kind of interpersonal need-supportive or need-thwarting teaching style is more associated with positive consequences in physical education? - Leo, Francisco (2022)
Purpose: Based on a multilevel approach (individual and class level), this study aimed to test which need-supportive/thwarting teaching styles were more closely associated with students’ motivation and other positive physical education (PE) out-of-school consequences. Method: Participants were 654 primary (n = 385) and secondary (n = 269) PE students (Mage = 11.96 ± 1.95; boys = 317 and girls = 337). Results: The three need-supportive teaching behaviors were related to autonomous motivation, PE importance and usefulness, and the intentions to practice physical activity at the individual level; the role of competence support at both individual and class levels is highlighted. Competence-thwarting style was also negatively related to autonomous motivation at both levels, and jointly to relatedness-thwarting behaviors positively to a motivation at the individual level. Conclusion: Our results provide insight into how the specific type of interpersonal styles adopted by teachers can be decisive to achieve positive PE outcomes in and out of school.